Perceptions, use and attitudes of pharmacy customers on complementary medicines and pharmacy practice - Bailey Michael; Spitzer Ondine; Wilkinson Jenny M; Tiralongo Evelin; Braun Lesley A; Poole Susan; Dooley Michael (BMC, 2010)
Abstract Background Complementary medicines (CMs) are popular amongst Australians and community pharmacy is a major supplier of these products. This study explores pharmacy customer use, attitudes and perceptions of complementary medicines, and their expectations of pharmacists as they relate to these products. Methods Pharmacy customers randomly selected from sixty large and small, metropolitan and rural pharmacies in three Australian states completed an anonymous, self administered questionnaire that had been pre-tested and validated. Results 1,121 customers participated (response rate 62%). 72% had used CMs within the previous 12 months, 61% used prescription medicines daily and 43% had used both concomitantly. Multivitamins, fish oils, vitamin C, glucosamine and probiotics were the five most popular CMs. 72% of people using CMs rated their products as 'very effective' or 'effective enough'. CMs were as frequently used by customers aged 60 years or older as younger customers (69% vs. 72%) although the pattern of use shifted with older age. Most customers (92%) thought pharmacists should provide safety information about CMs, 90% thought they should routinely check for interactions, 87% thought they should recommend effective CMs, 78% thought CMs should be recorded in customer's medication profile and 58% thought pharmacies stocking CMs should also employ a complementary medicine practitioner. Of those using CMs, 93% thought it important for pharmacists to be knowledgeable about CMs and 48% felt their pharmacist provides useful information about CMs. Conclusions CMs are widely used by pharmacy customers of all ages who want pharmacists to be more involved in providing advice about these products.